2014
DOI: 10.1002/2012ja018585
|View full text |Cite
|
Sign up to set email alerts
|

Pi2 pulsation simultaneously observed in the E and F region ionosphere with the SuperDARN Hokkaido radar

Abstract: We investigated Pi2 pulsations in the nightside ionosphere that began at 14:15 UT (2315 LT) on 11 July 2010, and they were observed with high-temporal (8 s) resolution by beam 4 of the Super Dual Auroral Radar Network (SuperDARN) Hokkaido radar. These pulsations were simultaneously observed in both the ground/sea scatter echoes reflected from the F region height and in ionospheric echoes from field-aligned irregularities in the sporadic E s region. They had the same period of 110 s and approximately no phase l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…These observations supported the Direct Response Bursty Bulk Flow model (DR‐BBF), in which ground instruments directly sense compressional waves generated by BBF braking [ Kepko and Kivelson , ]. By contrast, Teramoto et al [] compared SuperDARN Hokkaido radar Pi2 observations with theoretical predictions and suggested that a cavity mode together with the contribution of an Alfvén wave can account for some midlatitude Pi2s. More recently, Teramoto et al [] used multipoint observations from three midlatitude SuperDARN radars, three Time History of Events and Macroscale Interactions During Substorms (THEMIS) satellites, and ground magnetometers to study the latitudinal dependence of Pi2 frequency near the plasmapause.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…These observations supported the Direct Response Bursty Bulk Flow model (DR‐BBF), in which ground instruments directly sense compressional waves generated by BBF braking [ Kepko and Kivelson , ]. By contrast, Teramoto et al [] compared SuperDARN Hokkaido radar Pi2 observations with theoretical predictions and suggested that a cavity mode together with the contribution of an Alfvén wave can account for some midlatitude Pi2s. More recently, Teramoto et al [] used multipoint observations from three midlatitude SuperDARN radars, three Time History of Events and Macroscale Interactions During Substorms (THEMIS) satellites, and ground magnetometers to study the latitudinal dependence of Pi2 frequency near the plasmapause.…”
Section: Introductionmentioning
confidence: 70%
“…However, except for the compressional wave components ( E y and B z ), the other electric field and magnetic field components ( E x , B x , and B y ) from THD oscillated with much smaller amplitudes, as can be seen in Figure . Therefore, a mixture of other wave modes, such as propagating fast waves and/or shear Alfvén waves, together with a predominant standing fast wave, is a plausible scenario [ Teramoto et al , ; Lysak et al , ].…”
Section: Observations and Analysismentioning
confidence: 99%
“…Although radar observations are capable of investigating the spatial structure of Pi2 pulsations at mid latitudes (36°-60°), only a few studies have investigated Pi2 pulsations by using the SuperDARN radars at mid latitudes (Ponomarenko et al 2003;Gjerloev et al 2007;Frissell et al 2011;Teramoto et al 2014). To investigate generation mechanisms of Pi2 pulsations, multipoint observations are needed because Pi2 pulsations are globally excited in the mid and low latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…The global nature of Pi2 wave propagation presents challenges for modeling these pulsations. Pi2 pulsations are observed by spacecraft in a variety of orbits [e.g., Takahashi et al ., , ; Sutcliffe and Lühr , , ; Luo et al ., ], by ground magnetometers [e.g., Saito et al ., ; Samson , ; Yumoto , ; Shinohara et al ., ], and by radars that measure ionospheric flows [e.g., Ponomarenko et al ., ; Gjerloev et al ., ; Teramoto et al ., ]. Global MHD models are limited in describing higher frequency pulsations.…”
Section: Introductionmentioning
confidence: 99%